Study on the feasibility of an ECVET system for appprentices (test phase) : final report - Gelibert, Didier [Verfasser]; Maniak, Richard [Verfasser] (My University, 2007)
In the frame of the feasibility studies related to ECVET device ordered by the DGEAC of the European Commission, the study ECVET Connexion focuses specifically on the perspectives of implementation in the initial vocational education and training provision. The study study, on the one hand, aims at analysing the IVET system in Europe from the angle of the training offer (nature, organisation, programs, offer delivering, etc.); on the other hand, at identifying the obstacles to the implementation of the proposed ECVET mechanism; and to formulate recommendations favouring its development. (BIBB-Doku)
ecvet connexion
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Europäisches Leistungspunktesystem; Berufsbildung; Europa